The Effect of Differentiated Learning in Problem Based Learning on Cognitive Learning Outcomes of High School Students - Azmy Almas Dalila; Siti Rahmah; Winny Liliawati; Ida Kaniawati (Postgraduate, University of Mataram, 2022)
This study aims to investigate the effect of differentiated learning in the Problem Based Learning model on the cognitive learning outcomes of high school students. This research uses a quasi-experimental approach with a Nonequivalent Control Group research design. The research sample was selected using a purposive sampling technique with a total sample of 70 students of class X in one of senior high schools in Cimahi city, Bandung. The instrument used consisted of 4 reasoned multiple choice questions about momentum and impulses to measure students' cognitive learning outcomes. The results showed that the average value of N-Gain in the experimental class was 0.81 in the high category and in the control, class was 0.42 in the medium category. Statistical results show that the value of Asymp.Sig is 0.00 > 0.05. That is, there is an effect of differentiated learning in the Problem Based Learning (PBL) model on the cognitive learning outcomes of high school students on physics material